SYNTHESIS AND CHARACTERIZATION OF ZNO NANOPARTICLES USING LEAF EXTRACT OF RHIZOPHORA MUCRONATA AND EVALUATION OF THEIR ANTIMICROBIAL EFFICACY (World Journal of Current Medical and Pharmaceutical Research, 2019)
Nanotechnology is a developing interdisciplinary field of research interspersing material science, bionanoscience, and technology. Nanoparticles are studied extensively for their specific catalytic, magnetic, electronic, optical, antimicrobial, wound healing and antiinflammatory properties. The main aim of the present study was to synthesize ZnO nanoparticles using the aqueous extract of Rhizophora mucronata leaves and to evaluate their antimicrobial efficacy against some selected microbes. The synthesis Zn nanoparticles were characterized by UV/VIS spectroscopy, particle size analyzer and Scanning Electron Microscopy. The synthesized Zn nanoparticles showed significant antimicrobial activity against Gram-positive and Gram-negative bacteria as well as against a fungal strain. .A clear zone inhibition was measured;40.05mm±0.137 for Staphylococcus aureus, and 36.15 mm ± 0.304 for Escherichia coli that comparably better result than a standard antibiotic. Thus from this study, it can be concluded that rhizophora mucronata extracts can be effectively used for synthesizing Zno nanoparticles. This study also suggests that green synthesized Zn nanoparticles can be used as an alternative to existing antimicrobial agents.